Sweet and spicy crispy Nori rolls / Stefanus Robert - Robert, Stefanus (2022)
I have been given a task to running a business as a part of my assignment project. As a result, I decide to open and run a small business which, it is making Crispy Nori Rolls or also called as Crispy Seaweed Rolls. For modal, I refer to the order that customers make. I make the Crispy Nori Rolls by myself and put into the container to make sure it easy to be sold. Even, I’m a man, I believe I still can easy to make it after many times of practice, so don't judge a man. Other than that, making this snack as a business before 1 week of celebration of Gawai Dayak Day’s, could help the customers and myself, so the customers could add one more type of snack in their list on Gawai Day’s; so, 1 thought it could give me some more income. My objectives were, to ensure that my product meet customer’s taste and their expectations. I am hope, I could continue this business in celebration of Christmas Day’s this year that almost come and also in future. Besides, I choose this business as one way to meet new people and also develop myself. Through this career involvement, I learnt something new and that is how to develop my self-image, improving my confidence and obtaining new skills. I can also be able to widen my knowledge on how to make some food and marketing strategies. Although the Covid-19 pandemic situation still happening, but it does not lessen my spirit to learn, to make and runs the business. Thus, I decided to continue being in this business as it brought me so much benefits and profit that I could get, like any other small businessman.